2018
DOI: 10.1002/ejp.1329
|View full text |Cite
|
Sign up to set email alerts
|

The association of adverse childhood experiences and of resilience with chronic noncancer pain in the German adult population – A cross‐sectional survey

Abstract: Background Adverse childhood experiences (ACE) might predispose to and resilience might protect against chronic noncancer pain (CNCP). We studied whether ACE are positively associated with CNCP, whether resilience was negatively associated with CNCP and whether resilience buffered a potential association of ACE with CNCP. Methods A cross‐sectional survey (N = 2,425) representative for the adult German general population was conducted in 2013. The following questionnaires were used: Chronic Pain Grade Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 35 publications
1
8
0
7
Order By: Relevance
“…Our search identified 8320 articles, from which we included 85 studies reported in 87 articles ( Figure 1 ). 73 studies used a cross-sectional (Afifi et al, 2016 ; 2013 ; Alhalal et al, 2018 ; Anno et al, 2015 ; Badley et al, 2019 ; Baiden et al, 2021 ; Barron, 1997 ; Bendixen et al, 1994 ; Bottiroli et al, 2018 ; Brennenstuhl & Fuller-Thomson, 2015 ; Brown et al, 2018 ; Chartier et al, 2007 , 2010 ; Coles et al, 2015 ; Dennis et al, 2019 ; Díaz-Olavarrieta et al, 2002 ; England-Mason et al, 2018 ; Eriksen et al, 2016 ; Fowler et al, 2020 ; 2009 ; 2011 ; Hammond & Colman, 2020 ; Hanlon et al, 2020 ; Hart-Johnson & Green, 2012 ; Häuser et al, 2018 ; Jamieson & Steege, 1997 ; Jiao et al, 2015 ; Kamiya et al, 2016 ; Kascakova et al, 2020 ; Lee et al, 2009 ; Lin et al, 2021 ; Mays et al, 2021 ; McBeth et al, 2015 ; Nicol et al, 2016 ; Noteboom et al, 2021 ; Park et al, 2014a ; Pebole et al, 2022 ; Pierce et al, 2020 ; Reuchlein et al, 2016 ; Riedl et al, 2019 ; Sachs-Ericsson et al, 2007 ; 2017 ; Schrepf et al, 2018 ; Scott et al, 2011 ; Sheikh, 2018 , 2019 ; Shields et al, 2015 ; Sprang et al, 2020 ; Springer et al, 2007 ; Stickley et al, 2015 ; Talley et al, 1998 ; 1994 ; Tietjen et al, 2009 ; 2010 ...…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Our search identified 8320 articles, from which we included 85 studies reported in 87 articles ( Figure 1 ). 73 studies used a cross-sectional (Afifi et al, 2016 ; 2013 ; Alhalal et al, 2018 ; Anno et al, 2015 ; Badley et al, 2019 ; Baiden et al, 2021 ; Barron, 1997 ; Bendixen et al, 1994 ; Bottiroli et al, 2018 ; Brennenstuhl & Fuller-Thomson, 2015 ; Brown et al, 2018 ; Chartier et al, 2007 , 2010 ; Coles et al, 2015 ; Dennis et al, 2019 ; Díaz-Olavarrieta et al, 2002 ; England-Mason et al, 2018 ; Eriksen et al, 2016 ; Fowler et al, 2020 ; 2009 ; 2011 ; Hammond & Colman, 2020 ; Hanlon et al, 2020 ; Hart-Johnson & Green, 2012 ; Häuser et al, 2018 ; Jamieson & Steege, 1997 ; Jiao et al, 2015 ; Kamiya et al, 2016 ; Kascakova et al, 2020 ; Lee et al, 2009 ; Lin et al, 2021 ; Mays et al, 2021 ; McBeth et al, 2015 ; Nicol et al, 2016 ; Noteboom et al, 2021 ; Park et al, 2014a ; Pebole et al, 2022 ; Pierce et al, 2020 ; Reuchlein et al, 2016 ; Riedl et al, 2019 ; Sachs-Ericsson et al, 2007 ; 2017 ; Schrepf et al, 2018 ; Scott et al, 2011 ; Sheikh, 2018 , 2019 ; Shields et al, 2015 ; Sprang et al, 2020 ; Springer et al, 2007 ; Stickley et al, 2015 ; Talley et al, 1998 ; 1994 ; Tietjen et al, 2009 ; 2010 ...…”
Section: Resultsunclassified
“…Three studies covered multiple countries (Lee et al, 2009 ; Reuchlein et al, 2016 ; Scott et al, 2011 ), ACEs were collected through self-reported questionnaires ( n = 76) (Afifi et al, 2016 ; 2013 ; Alhalal et al, 2018 ; Anda et al, 2010 ; As-Sanie et al, 2014 ; Bacon & White, 2022 ; Badley et al, 2019 ; Baiden et al, 2021 ; Barron, 1997 ; Bellis et al, 2018 ; Bendixen et al, 1994 ; Bottiroli et al, 2018 ; Bradford et al, 2012 ; Brennenstuhl & Fuller-Thomson, 2015 ; Brown et al, 2018 ; Chartier et al, 2007 , 2010 ; Coles et al, 2015 ; Daily et al, 2022 ; Dennis et al, 2019 ; Díaz-Olavarrieta et al, 2002 ; England-Mason et al, 2018 ; Eriksen et al, 2016 ; Fowler et al, 2020 ; Fuller-Thomson et al, 2009 ; 2011 ; Hammond & Colman, 2020 ; Hanlon et al, 2020 ; Hart-Johnson & Green, 2012 ; Häuser et al, 2012 ; 2018 ; Jamieson & Steege, 1997 ; Ju et al, 2020 ; Kamiya et al, 2016 ; Kascakova et al, 2020 ; Kopec & Sayre, 2005 ; Li et al, 2022 ; Lin et al, 2021 ; Mays et al, 2021 ; McBeth et al, 2015 ; Nicol et al, 2016 ; Park et al, 2016 ; Pebole et al, 2022 ; Pierce et al, 2020 ; 2022 ; Piontek et al, 2021 ; Rahal et al, 2020 ; Raphael et al, 2001 ; Reuchlein et al, 2016 ; Riedl et al, 2019 ; Schlauch et al, 2022 ; Schrepf et al, …”
Section: Resultsunclassified
“…These include physical, emotional or sexual abuse, neglect, poverty, parental incarceration, parental divorce, domestic violence or parental mental health disorders. The ACEQ has been used in several studies of early‐life adversity (Häuser et al., 2019; Merrick et al., 2019) and until recently was the primary tool of the Centres for Disease Control—Kaiser Adverse Childhood Experiences longitudinal population‐level cohort study ( https://www.cdc.gov/violenceprevention/childabuseandneglect/acestudy, last accessed Sept. 11, 2019). The Brief Illness Perceptions Questionnaire (BIPQ). The BIPQ is a shortened 10‐item version of the full Illness Perceptions Questionnaire that taps the primary domains of Leventhal's Common Sense Model of Illness Representations (Leventhal et al., 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Die Lebenszeitprävalenz der sexualisierten Gewalt im Kindes-und Jugendalter lag in unserer Studie bei 18,2 % und war damit höher als bisher für Deutschland berichtet [18,21,32]. Gründe hierfür könnten der Pilotcharakter der Studie mit einer überschaubaren Stichprobengröße und der breit gewählte Begriff der sexualisier-▶Abb.…”
Section: Diskussionunclassified
“…In Deutschland gab es seit den 2010er Jahren mehrere retrospektive Querschnittsstudien mit repräsentativen Bevölkerungsstichproben volljähriger Personen aus Privathaushalten zur Häufigkeit sexualisierter Gewalt in Kindheit und Jugend [17][18][19][20][21][22][23][24][25], wobei die Daten der sogenannten MiKADO-Studie bisher nicht wissenschaftlich begutachtet veröffentlicht wurden. Je nach Definition sexualisierter Gewalt, des Schutzalters, der einbezogenen Aus-kunftsquellen und Tätergruppen wurden Lebenszeitprävalenzen zwischen 2,5 % [22] und 13,9 % [21] identifiziert, die zudem nicht auf eine Rückläufigkeit dieser gesamtgesellschaftlichen Herausforderung hinweisen.…”
Section: Introductionunclassified